The Association Between Circulating Trans Fatty Acids and Thyroid Function Measures in U.S. Adults - Wang, Xiaoqian; Jiang, Fengjuan; Chen, Wenqing; Yuan, Hui; Li, Yuan (Frontiers in Endocrinology, 2022)
Abstract Background: There has been controversial evidence regarding the effect of trans fatty acids (TFAs) on thyroid function in animal studies, and the epidemiological studies are lacking. We aimed to investigate the potential associations between circulating TFAs and thyroid function biomarkers in a U.S. adult population sample. Methods: We performed a cross-sectional survey with 626 adults aged ≥20 years who participated in the National Health and Nutrition Examination Survey (NHANES) 2009–2010. Multivariable linear regression models were constructed to elucidate the relationships between circulating concentrations of TFAs (palmitelaidic acid, vaccenic acid, elaidic acid, linoelaidic acid and the sum of the four TFAs) and a panel of thyroid function measures. Results: For 626 adults, positive associations were found between palmitelaidic acid, elaidic acid and total thyroxine (TT4), between palmitelaidic acid and total triiodothyronine (TT3), and between linolelaidic acid and thyroid stimulating hormone (TSH), while linolelaidic acid was negatively associated with free thyroxine (FT4) (all P<0.05). Besides, the four TFAs and the sum TFAs were positively associated with free triiodothyronine (FT3). Vaccenic acid, elaidic acid, linoelaidic acid and the sum TFAs were positively associated with FT3/FT4, while the four TFAs and the sum TFAs were negatively associated with FT4/TT4 (all P<0.05). In stratified analysis, the associations between thyroid function measures and the ratios remained significant in female. For men, linolelaidic acid was negatively associated with FT4 and elaidic acid and the sum TFAs were positively associated with FT3. Furthermore, the associations between TFAs and FT3/FT4 remained significant. Conclusion: Our findings revealed that TFAs exposure was associated with serum biomarkers of thyroid function. More researches are needed to evaluate the long-term health outcomes of these findings.